2016
DOI: 10.1155/2016/1706915
|View full text |Cite
|
Sign up to set email alerts
|

Giant Primary Schwannoma of the Left Nasal Cavity and Ethmoid Sinus

Abstract: A unilateral tumour in the nasal cavity or paranasal sinuses is commonly caused by polyps, cysts, and mucoceles, as well as invasive tumours such as papillomas and squamous cell carcinomas. Schwannomas, in contrast, are rare lesions in this area (Minhas et al., 2013). We present a case of a 52-year-old female who presented with a 4-year progressive history of mucous hypersecretion, nasal obstruction, pain, and fullness. Imaging of the paranasal sinuses showed complete opacification of the entire left nasal cav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…Mitra B et al [2] , Vaidya MM et al [3] , Dhawle MS et al [4] and Mangubat EZ et al [6] documented schwannoma in male patient. On the contrary, Singh M et al [5] , Mosalleum EMA [7] and Wong E et al [8] reported the lesion in female patients in their case reports.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Mitra B et al [2] , Vaidya MM et al [3] , Dhawle MS et al [4] and Mangubat EZ et al [6] documented schwannoma in male patient. On the contrary, Singh M et al [5] , Mosalleum EMA [7] and Wong E et al [8] reported the lesion in female patients in their case reports.…”
Section: Discussionmentioning
confidence: 92%
“…Wong E et al [8] reported a case of sinonasal schwannoma in sixth decade in their case report. Mitra B et al [2] , Vaidya MM et al [3] , Dhawle MS et al [4] and Mangubat EZ et al [6] documented schwannoma in male patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative biopsy is considered to diagnose these type of cases but excisional biopsy can also be done based upon clinical and radiological assessment [10]. Schwannomas appear as gelatinous, cystic, well circumscribed encapsulated masses and are usually amenable for endoscopic removal [11]. On histopathological examination, schwannomas exhibit Antoni A and Antoni B patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it is difficult to distinguish between OEC tumors and schwannomas, since both tumors arise from glial cells with a shared developmental origin (the neural crest, [51]), as well as many similar morphological and molecular characteristics (reviewed in [6]). The schwannomas that are so easily confused with OEC tumors are usually termed anterior cranial fossa schwannomas or olfactory groove schwannomas (OGS) but can also occasionally be found in the nasal cavity and paranasal sinuses (nasoethmoid schwannomas) [71][72][73][74][75]. These schwannomas are rare; to date, approximately 45 cases (without neurofibromatosis/schwannomatosis) have been reported in the literature [76,77].…”
Section: Why Is It Difficult To Distinguish Between Oec Tumors and Scmentioning
confidence: 99%